The PDMA handbook of new product development - Kahn, Kenneth B. (Wiley, 2005)
"The PDMA Handbook of New Product Development, Second Edition provides a comprehensive, updated picture of what you as a manager need to know for effective new product development. The book's concise, map-like detail acts as a compass, offering practical information pertaining to every stage of the product development process -- from idea generation to launch to the end of the life cycle. Whether you're a novice or an expert, this edition is ideal as it provides both fundamentals and reliable information on advanced and emerging concepts such as accelerated product development, new product development globalization and benchmarking, and Web-based concept development"--Resource description page.